(x^2y^3+6x^4y^2)-(5x^2y^3-2x^4y^2)

The difference of the polynomial is ?

Simplify

Thank you for the opportunity to help you with your question!

(x^2y^3+6x^4y^2)-(5x^2y^3-2x^4y^2) =

= x^2y^3+6x^4y^2 - 5x^2y^3 + 2x^4y^2

= (x^2y^3 - 5x^2y^3) + (6x^4y^2 +2x^4y^2)

= -4x^2y^3 + 8x^4y^2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up